Active Pause as a Factor of Change Associated with Healthy Lifestyle, in Students of the Tenth Semester of Medicine in the Industrial University of Santander (UIS) Bucaramanga- Colombia - Almeida Espinosa, Alexander; Gafaro Rojas, Aurora Ines; Angulo Silva, Mary Lupe (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
In this study, the objective was to identify the impact of active breaks in tenth semester students of medicine at the Industrial University of Santander (UIS) Bucaramanga - Colombia, which promotes a healthy lifestyle and thus reduces the appearance of disabling periods, which directly affect academic performance. The methodology used is descriptive - exploratory. It was concluded that active pauses improve physical condition, increase academic performance, students' absences remain constant and improve their quality of life.